Expression of PR genes and genes of heat shock proteins of potato plants in vitro under infection with ring rot and heat stress - Nurminsky, V.N.; Stolbikov, A.S.; Pomortsev, A.V.; Perfileva, A.I. (Вiopolymers and Cell, 2018)
Aim. The changes in expression of the HSP101, HSP60, and HSP17.8 genes in tissues of potato plants of varieties Lukyanovsky under in vitro heat treatment and infection with a ring rot pathogen Clavibacter michiganensis ssp. sepedonicus (Cms) were investigated. Methods. These changes were assessed at the transcript and protein levels. Results. It was shown that under heat treatment at 39°C for 2 h, the maximum accumulation of HSP101 was observed. In control experiments, the plants of the two varieties showed neither synthesis of HSP101, HSP60 and HSP17.8 proteins nor expression of the HSP101, HSP60 and HSP17.8 genes. Infection without heat treatment induced HSP60 expression. Infection suppressed activation of HSP genes upon heat stress. Additionally, infection of potato plants by Cms caused an increase in transcription of PR-2 and PR-4 genes. Conclusions